Uji Kelayakan Validasi Praktisi Buku Panduan Praktik Kewirausahaan Pada Mahasiswa Program studi Pendidikan Ekonomi - Kusworo Kusworo; Purwati Yuni Rahayu (Faculty of training and education, Pamulang university, 2021)
ABSTRACTThis study aims to determine the feasibility of practitioner validation of the product development of entrepreneurship practice guidebooks for students of the Pamulang University Economic Education study program. The approach used in this research is a quantitative approach. This research is part of the Borg & Gall development research procedure. The data analysis technique used by the researcher in this study is descriptive statistics. The results of the study which are the results of the feasibility test of expert practitioner validation get a score of 83.13 with very good criteria. In detail, it can be described as follows: 1). The content feasibility assessment indicator obtained a score of 84.62 with very good criteria; 2). The presentation feasibility assessment indicator obtained a score of 81.82 with very good criteria; 3). The indicator for the assessment of the presentation of practical book learning obtained a score of 82.50 with very good criteria; and 4). The indicator for the assessment of the benefit aspect obtained a score of 83.33 with very good criteria. The results of this study indicate that the validation of the feasibility of the practitioner of the entrepreneurship practice guidebook gets a very good category and is feasible to use.Keywords: Practitioner Validity; Practice Handbook; EntrepreneurshipABTRAKPenelitian ini bertujuan untuk mengetahui kelayakan validasi praktisi atas produk pengembangan buku panduan praktik kewirausahaan pada mahasiswa program studi Pendidikan ekonomi Universitas Pamulang. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kuantitatif. Penelitian ini merupakan bagian dari prosedur penelitian pengembangan Borg & Gall. Teknik analisis data yang digunakan oleh peneliti dalam penelitian ini yaitu statistik deskriptif. Hasil penelitian yang merupakan hasil uji kelayakan validasi ahli praktisi mendapatkan penilaian skor 83,13 dengan kriteria sangat baik. Secara rinci dapat dijabarkan sebagai berikut: 1). Indikator penilaian kelayakan isi memperoleh skor nilai 84,62 dengan kriteria sangat baik; 2). Indikator penilaian kelayakan penyajian memperoleh skor nilai 81,82 dengan kriteria sangat baik; 3). Indikator penilaian penyajian pembelajaran buku praktik memperoleh skor 82,50 dengan kriteria sangat baik; dan 4). Indikator penilaian aspek manfaat memperoleh skor 83,33 dengan kriteria sangat baik. Hasil penelitian tersebut menunjukkan bahwa validasi kelayakan praktisi buku panduan praktik kewirausahaan mendapatkan kategori sangat baik dan layak untuk digunakan.Kata kunci: Validitas Praktisi; Buku Panduan Praktik; Kewirausahaan